Influence of an Ice Storm on Aboveground Biomass of Subtropical Evergreen Broadleaf Forest in Lechang, Nanling Mountains of Southern China - Fang Zhang; Guangyi Zhou; Motoshi Hiratsuka; Kazuo Tanaka; Yasushi Morikawa (International Journal of Forestry Research)
This study focuses on the influence of the 2008 ice storm in China and subsequent forest rehabilitation dynamics up until 2011. All seven plots studied exhibited significant damage, with the total number of damaged trees varying between 63 and 92%. In addition, most trees suffered stem bending in 2008 and the extent of damage varied with tree diameter at breast high (DBH). Relationships between loss of biomass as dead trees and stand characteristics were analyzed by multiple stepwise regression. The results showed that the decrease in biomass (Y) could be related to altitude (X1), slope (X2), and aboveground biomass (AGB) in 2008 (X5) according to the following formula: Y=−0.02456X1+0.2815X5−1.480X2+51.23. After 2 to 3 years, tree numbers had declined in all seven plots. The mean increase in AGB (4.9 t ha−1) for six of the plots was less than the biomass loss as dead trees (9.4 t ha−1) over the 3 year periods. This corresponds to a release of CO2 to the atmosphere for each plot. Therefore, the forests of Lechang in the Nanling Montains have probably acted as a carbon source to the atmosphere for a short period after the 2008 ice storm.